Global, regional, and national burden of uterine cancer among women aged 50 years and older from 1990 to 2021: a systematic analysis for the global burden of disease study 2021 - Tingting Feng; Wei Li; Qin Wang; Jing Yang; Fujin Shen (Journal of Health, Population and Nutrition)
Abstract Background Uterine cancer poses a growing global health threat, with rising incidence among women aged ≥ 50 years. This study aimed to evaluate its disease burden across regions and nations. Methods Using Global Burden of Disease 2021 data, we analyzed the incidence, mortality, disability-adjusted life years (DALYs), and trends via estimated annual percentage change (EAPC), decomposition, inequality analyses, and Bayesian Age-Period-Cohort modeling for 2022–2040 projections. Results In 2021, global uterine cancer cases among women ≥ 50 years reached 414,754 (95% UI: 370,388–453,502), causing 90,509 deaths (95% UI: 78,633–101,441) and 2,189,261 DALYs (95% UI: 1,920,396–2,446,737). Age-standardized incidence rate (ASIR) rose (EAPC = 0.56, 1990–2021), while mortality and DALYs declined. High-income North America had the highest ASIR (128/100,000), with the United States, China and Russia leading new cases. High Socio-demographic index (SDI) regions exhibited widening disparities, evidenced by a 21% increase in the slope index of inequality (SII) for incidence (47 in 1990 to 57 in 2021) and concentration indices (CI) rising from 0.33 (95% CI: 0.28, 0.37) in 1990 to 0.35 (95% CI: 0.29, 0.4) in 2021. Population growth drove 132.55% of DALY changes, outweighing epidemiological (-32.95%) and aging (0.4%) factors. Projections suggest declining ASIR, the age-standardized mortality rate (ASMR), and DALY rates by 2040, yet absolute cases will rise to 617,571 new cases, 131,961 deaths, and 2,851,768 DALYs. Conclusions Despite declining mortality and DALY rates, uterine cancer incidence continued to increase globally, driven by population growth. High-income regions faced disproportionate burdens, with persistent health inequities. Projected absolute case growth demands urgent prioritization of equity-oriented screening, prevention, and resource allocation. Governments must integrate targeted interventions with global aging policies to address this dual burden of epidemiological transition and health inequity.